Enhancing Visual Intelligence Through a Triplet Representation-Based Virtual Laboratory on Chemical Equilibrium Shifts - Damayanti, Dini; Dwiningsih, Kusumawati; Arivi, Maharani Agustina (Jurnal Tadris Kimiya, 2025)
This research examined the validity, practicality, and effectiveness of virtual laboratory based on triplet representation to enhance students' visual intelligence in chemical equilibrium shifts. Using the Research & Development (R&D) method with the Analysis, Design, Development, Implementation, and Evaluation (ADDIE) model, this study involved 31 students from MAN 2 Gresik. The instruments used included validation questionnaire, student response questionnaire, and pre-posttest sheets. The results showed the media achieved very good validity with a mode of four, very practical with practicality test reached 94.08% and effective to enhance visual intelligence in chemical equilibrium shifts with significance value of 0.000 (< 0.05) on Wilcoxon Signed Rank and medium-high category N-Gain. This virtual laboratory based on triplet representation is proven to be valid, practical, and effective in enhancing students' visual intelligence on chemical equilibrium shift. This media can be an innovative solution for digital learning and a cost-effective alternative for schools that lack laboratory facilities.